Scottish Identity in Trainspotting - Plíhalová, Veronika (Univerzita Pardubice, 2021)
The bachelor thesis deals with national identity, and in its majority the Scottish national identity. It is divided in two parts, the first of which aims to provide theoretical background on the subject of national identity and its features, and subsequently discusses the Scottish historical development with respect to the parallel development of identity and literature. The findings are illustrated on the novel Trainspotting, specifically on the author and three characters.
Skotská identita v Trainspotting
Keywords: skotská národní identita; národní cítění; národ; Trainspotting; Welsh, Irvine; Renton, Mark; Edinburgh; Británie; Scottish national identity; national sentiment; nation; Trainspotting; Welsh, Irvine; Renton, Mark; Edinburgh; Britain